Caminhos criativos: uma experiência em composição coreográfica na dança de salão - CONCEIÇÃO, Everton Pires da (2018)
This research aims to analyze my experiences as a creative choreographer in the dance hall. These are questions that entice me to think how to create dances, which the artist's feelings involved? To answer these questions and dialogue with authors, LOBO/ NAVAS (2008) and ROBATTO (1994), dealing with the creative processes in dance, PERNA (2001), the historical background of ballroom dancing in Europe and Brazil, in choreography, PAIXÃO (2003), among others. As a result, I share my experiences after I started working on my creative processes in dance choreography. Soon, I also a reflection of the qualities of the artist in ballroom dancing.